The pattern of Atopy in Childhood Nephrotic Syndrome-A Tertiary Hospital Study (Bangladesh Journal of Child Health, 2021)
Background: Idiopathic nephrotic syndrome is a common renal disease in children. Various atopic disorders are found in 30%-60% cases with childhood nephrotic syndrome.Objective: To evaluate the association of atopic disorders with childhood idiopathic nephrotic syndrome.Methods: This case-control study was conducted in the Department of Paediatrics, Sir Salimullah Medical College Hospital from January 2012 to December 2012. Fifty children of idiopathic nephrotic syndrome between 2 to 10 years of age were included and the diagnosis was based on history, clinical features and laboratory evidence. Age and sex-matched controls were taken from pediatrics outdoor who attended for problems other than nephrotic syndrome. Data regarding atopic disorders in both groups were collected and then analyzed.Results: Mean ages in this study were 5.32±2.88 years and 5.34±2.87 years in case and control respectively. The male-female ratio was 1.7: 1 in both groups. A positive history of atopy was present in 46.0% of cases and 20.0% in controls. Atopic disorders were asthma (42.0% vs. 20.0%), allergic rhinitis (30% vs. 10%), atopic dermatitis (0.0% vs. 2.0%) and allergic conjunctivitis (0.0% vs. 2.0%) found in cases and controls respectively. Bronchial asthma was frequently (37.5%) found in frequent relapse nephrotic syndrome compared to infrequent relapse and the first attack of nephrotic syndrome.Conclusion: Children with idiopathic nephrotic syndrome had a higher incidence of atopy. Asthma and allergic rhinitis was found as common atopic disorders associated with childhood idiopathic nephrotic syndrome.BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 6-9